2022
DOI: 10.3389/fneur.2022.1041099
|View full text |Cite
|
Sign up to set email alerts
|

Moderate systemic therapeutic hypothermia is insufficient to protect blood-spinal cord barrier in spinal cord injury

Abstract: Blood–spinal cord barrier (BSCB) disruption is a pivotal event in spinal cord injury (SCI) that aggravates secondary injury but has no specific treatment. Previous reports have shown that systemic therapeutic hypothermia (TH) can protect the blood–brain barrier after brain injury. To verify whether a similar effect exists on the BSCB after SCI, moderate systemic TH at 32°C was induced for 4 h on the mice with contusion-SCI. In vivo two-photon microscopy was utilized to dynamically monitor the BSCB leakage 1 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Therefore, further research is needed to develop diagnostic and predictive prognostic models for acute TSCI, and a framework for identifying valuable biomarkers is also necessary to improve the accuracy of prognostic prediction. It has been shown that the blood-spinal cord barrier (BSCB) is disrupted by TSCI, leukocyte tra cking is also increased (21,22). Some in ammatory biomarkers, such as C-reactive protein (CRP ), IL-6 or monocyte chemotactic protein-1, can participate in the systemic in ammatory response and can be transported into the blood or cerebrospinal uid(8, 23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further research is needed to develop diagnostic and predictive prognostic models for acute TSCI, and a framework for identifying valuable biomarkers is also necessary to improve the accuracy of prognostic prediction. It has been shown that the blood-spinal cord barrier (BSCB) is disrupted by TSCI, leukocyte tra cking is also increased (21,22). Some in ammatory biomarkers, such as C-reactive protein (CRP ), IL-6 or monocyte chemotactic protein-1, can participate in the systemic in ammatory response and can be transported into the blood or cerebrospinal uid(8, 23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that the protective effect of CHA on blood–brain barrier integrity is likely the main mechanism underlying its protection against neuroinflammation. Previous studies have indicated that hyperthermia increases BBB permeability, while therapeutic hypothermia can have a protective effect [ 18 , 19 , 20 , 21 , 22 ]. Consistent with the literature, our data also confirm that CHA-induced hypothermia significantly prevents the loss of zo-1, preserving blood–brain barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells (ECs) play a key role in regulating selective transport and metabolic exchange between the blood and the spinal cord as a vital component of the BSCB (12). Post-SCI, ECs undergo regeneration at the site of injury; however, their functional attributes are markedly diminished relative to their healthy counterparts, spanning diminished barrier functionality to compromised substance transport (13,14).…”
Section: Introductionmentioning
confidence: 99%